TEACHING COMMUNICATION STRATEGIES TO THE COMPUTER PROGRAMMING STUDENTS - Mykytenko, Nataliya; Rozhak, Nataliia; Semeriak, Iryna (Advanced Education, 2019)
The successful functioning of computer programming specialists largely depends on their level of communicative competence, so a university course of English for specific purposes (ESP), aimed at its development, can be exceedingly useful in professional training of future computer programmers. To optimise the process of ESP learning we have outlined the verbal addresser-oriented strategies (stimulating strategy, emotional activity strategy, evaluation activity strategy, cooperative strategy and strategy of self-presentation) and elaborated a system of exercises for their development. It includes the following stages: 1) studying general foreign language by means of communication strategies; 2) studying ESP by means of communication strategies. To validate the effectiveness of the system of exercise we conducted experimental teaching of the 1st and 2nd-year students of the Faculty of Applied Mathematics and IT Technologies at Lviv Ivan Franko National University in 2016‒2017 academic year. It involved 144 participants. Efficiency of the system of exercises has been proved on the basis of the results obtained from pre- and post- experimental assessment of students from exposure groups and reference groups. Growth rate in students from exposure groups significantly exceeded the results in students from reference groups. Thus, the efficacy of the suggested system of exercises used for developing communication strategies in computer programming students has been proved.